Small fiber neuropathy and phosphorylated alpha-synuclein in the skin of E46K-SNCA mutation carriers. (August 2019) - Carmona-Abellan, Mar; Gabilondo, Inigo; Murueta-Goyena, Ane; Khurana, Vikram; Tijero, Beatriz; Luquin, María Rosario; Acera, Marian; Del Pino, Rocío; Gardeazabal, Jesús; Martínez-Valbuena, Ivan; Sanchez-Pernaute, Rosario; Gómez-Esteban, Juan Carlos
Abstract: Background and objective: In 2004 we described the E46K mutation in alpha-synuclein gene (E46K-SNCA), a rare point mutation causing an aggressive Lewy body disease with early prominent non-motor features and small fiber denervation of myocardium. Considering the potential interest of the skin as a target for the development of biomarkers in Parkinson's Disease (PD), in this work we aimed to evaluate structural and functional integrity of small autonomic nerve fibers and phosphorylated alpha-synuclein (p-synuclein) deposition in the skin of E46K-SNCA carriers as compared to those observed in parkin gene mutation (PARK2) carriers and healthy controls. Patients and methods: We studied 7 E46K-SNCA carriers (3 dementia with Lewy bodies, 2 pure autonomic failure, 1 PD and 1 asymptomatic), 2 PARK2 carriers and 2 healthy controls to quantify intraepidermal nerve fiber density and p-synuclein deposition with cervical skin punch biopsies (immunohistochemistry against anti PGP9.5/UCHL-1, TH and p-synuclein) and sudomotor function with electrochemical skin conductance (ESC) (SudoScan). Results: All E46K-SNCA carriers had moderate to severe p-synuclein deposits and small fiber neurodegeneration in different epidermal and dermal structures including nerve fascicles and glands, especially in carriers with Pure Autonomic Failure, while p-synuclein aggregates where absent in healthy controls and in one of two PARK2 carriers. The severity of the latter skin abnormalities in E46K-SNCA were correlated with sudomotor dysfunction (lower ESC) in hands ( p  = 0.035). Interpretation: These results together with our previous findings support the relevance of E46K-SNCA mutation as a suitable model to study small fiber neuropathy in Lewy body diseases. Highlights: The E46K-SNCA mutation is of interest given the rarity of this mutation. The results highlight the peculiarity of this mutation and reinforce the idea of peripheral tissue as a biomarker of the disease. SNCA-E46K mutation is very rare, and the fact that synuclein is altered make this mutation unique as an in vivo model of disease progression. There is a correlation between electroconductance and synuclein aggregates in these patients. For the first time, we describe the presence of peripheral nervous system peculiarities, in patients with a wide spectrum of phenotype and the same genotype.